2012
DOI: 10.1186/1471-2458-12-1106
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics related to the risk of adolescent internet addiction: a survey in Shanghai, China

Abstract: BackgroundParalleling the rapid growth in computers and internet connections, adolescent internet addiction (AIA) is becoming an increasingly serious problem, especially in developing countries. This study aims to explore the prevalence of AIA and associated symptoms in a large population-based sample in Shanghai and identify potential predictors related to personal characteristics.MethodsIn 2007, 5,122 adolescents were randomly chosen from 16 high schools of different school types (junior, senior key, senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 33 publications
3
84
2
1
Order By: Relevance
“…Moreover, the following Internet use variables were found to be associated with Internet addiction in adolescents: age of first exposure to the Internet [195], Internet use for entertainment purposes [63], frequency and length of Internet use [45,63,64,76], Internet access at home [61], Internet usage at an Internet café [70,78], the use of online gaming [46,52,69,196], social applications [45,46,52], and other Internet applications [69]. In addition to this, parental guidance with regards to Internet behaviours was reported to be associated with Internet addiction, specifically little parental communication about Internet use, rules about Internet times [41], and a lack of rules regarding Internet use [50].…”
Section: Internet Use Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the following Internet use variables were found to be associated with Internet addiction in adolescents: age of first exposure to the Internet [195], Internet use for entertainment purposes [63], frequency and length of Internet use [45,63,64,76], Internet access at home [61], Internet usage at an Internet café [70,78], the use of online gaming [46,52,69,196], social applications [45,46,52], and other Internet applications [69]. In addition to this, parental guidance with regards to Internet behaviours was reported to be associated with Internet addiction, specifically little parental communication about Internet use, rules about Internet times [41], and a lack of rules regarding Internet use [50].…”
Section: Internet Use Variablesmentioning
confidence: 99%
“…Sung and colleagues [51] used the Internet Addiction Proneness Scale -Short Form (KS-Scale) [88] in a sample of 73,238 adolescents in South Korea and reported that 3.0% and 11.9% of adolescents were at high risk and at potential risk for developing Internet addiction in South Korea, respectively [51]. On the other end of the spectrum, Xu et al [45] used the DRM 52 Scale of Internet use in a random sample of 5,122 adolescents in Shanghai, China with the result that 8.8% of adolescents in this sample were classified as Internet addicts. The only cross-cultural study of Internet addiction prevalence included two separate samples of 1,761 high school students in China and 1,182 students in the USA who were used in a longitudinal study by Sun et al [47] using the (CIUS), and showed that the prevalence rates were 5.8% in Chinese females, 15.7% in Chinese males, 9.7% in US females, and 7.3% in US males.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations